Representing Software Process in Description Logics: An Ontology Approach for Software Process Reasoning and Verification - Kabaale, Edward; Wen, Lian; Wang, Zhe; Rout, Terry (Springer, Cham., 2016)
Software process is critical for producing high quality software. However, software processes are usually described in natural language which makes it difficult to verify if they have been fully or how well implemented in complex software projects. It’s also hard for practitioners to implement processes from different standards and make sure they work harmonically, consistently and completely. Composition Tree (CT) notation, a Behavior Engineering approach has been successfully used to formalize software process in previous work. However, there are no reasoning tools for CT to automatically check and verify the modeled software processes. In this study we explore the synergy of software process modeling and Description Logics (DLs). Given the rich expressiveness of DLs and their efficient and automated reasoning support, DLs can be used to reason and verify software processes more effectively. We propose an algorithm for transforming CT software process model into a DL so that DL reasoning engines can be used to perform automated software process analysis.
Keywords: Software process; Composition tree; Description logics; Automatic